Study on the process of micro-arc oxidation TiO2 film for rapid detection of triethylamine. (1st August 2022) - Pan, Mingqiang; Shi, Zeming; Liu, Jizhu; Wang, Yangjun
Abstract: By taking into account the severe limitations of the triethylamine gas sensors, including the long response recovery time and the poor selectivity, it is still necessary to design and manufacture TEA-based gas sensors with improved sensing performance. Along these lines, the morphological operations on semiconductor metal oxide gas-sensitive materials are considered to be an effective method to enhance their sensing capabilities. Therefore, in this work, the micro-arc oxidation technology was used to prepare a TiO2 sensitive film for the detection of the TEA gas. Interestingly, the process parameters of the micro-arc oxidation mechanism have an important influence on the growth process of the TiO2 film. Consequently, choosing the appropriate current density, oxidation time, pulse width and electrolyte concentration characteristics is beneficial to control both the morphology and structure of the TiO2 film. The coupling relationship between the process parameters was thoroughly studied by performing an orthogonal array tests. More specifically, the optimum preparation conditions were the following: current density of 0.65A/cm 2, oxidation time of 4min, a pulse width of 1250 ms and electrolyte concentration of 7 g/L. The characterization of the micro-arc TiO2 sensitive film revealed that the surface of the film showed a large number of heterogeneous pore structures (with a diameter of about 2–3 μm) and some nano-sized pores, while the film thickness was 30 μm and exhibited a good continuity. The acquired gas sensing results indicate that the optimized micro-arc TiO2 film possesses a fast response and recovery (5 s, 52 s) to 100 ppm TEA and a detection limit of 0.9 ppm. Our work provides fruitful insights for the preparation of TEA gas-sensitive materials by enforcing the micro-arc oxidation technology.